Agency Costs of Outside Equity: Evidence From Start-Up Firms in Their First Two Years - Everett, Craig R. (Archives of Business Research, 2024)
This paper investigates the agency costs associated with outside equity infusions into 4928 randomly selected firms surveyed annually during their first two years of business. Sources of outside equity include angel investors, venture capital or private equity, other companies, or government sources. Changes in outside equity levels are significantly and positively associated with changes in the number of perquisite programs available to employees. These results are robust to controls for observable firm characteristics such as firm size and profitability.